Classroom English Learning Activities: Students' Facial Expressions with a Focus on Interpersonal Meanings - Dewi Rosmala; Vidya Setyaningsih (TLEMC (Teaching and Learning English in Multicultural Contexts), 2021)
Studies on facial expressions have been looked into from a variety of angles in earlier research. A prior study (Feng O'Halloran, 2012) examined how comic cartoons' facial expressions changed over time. There are, however, very few studies that concentrate on comic books as opposed to student facial expressions. The purpose of this study is to identify the facial expressions made by students as they learn English in a classroom setting. One student selected and recorded facial expressions during the teaching and learning process. The most frequently occurring portions of facial expressions are chopped out of a movie frame by frame in order to collect data. Then, using Martinec's framework (Martinec, 2001), all data are examined to determine the interpersonal meanings of the students' facial expressions. Facial expressions during the teaching and learning process are made an accomplishment for students as a result of this research's total contribution. Students' efforts to achieve their goals during the teaching and learning process are demonstrated by their passion, which is successfully created by the teacher through facial expressions.Â Keywords: ELL Classroom; Interpersonal meaning; Studentsâ€™ facial expression.